Tortor Mangiligi Dalam Upacara Sayur Matua Pada Masyarakat Simalungun Kajian Terhadap Nilai Sosial - Immanensia Tambun (Universitas Negeri Medan, 2017)
This study discusses the Tortor Mangiligi In Ceremony Sayur Matua At Simalungun Society Study on the Social Value.To discuss the above research purposes, used theories related to the research topic, such as Tortor understanding, understanding Sayur Matua, Social Values and Implementation Process.When the study are used in discussing Tortor Mangiligi In Ceremony Sayur Matua At Simalungun Society Study on Social Values for 3 (three) months, namely in June to August 2016. The study site is Dalig Raya, Pematang Raya, Simalungun. The population in this study is the traditional leaders of society Simalungun, Tortor Mangiligi video documentation, as well as actors in the ceremony Tortor Mangiligi Sayur Matua.Analisis data in this study using descriptive qualitative data collection techniques with literature study, observation, interviews, and documentation.The results showed that, Tortor Mangiligi implemented as a form of respect for his children for services, kindness and hard work to his parents, and as a family party of gratitude to our Creator for longevity given to the parents of the deceased. Through the stages of planning to carry out the funeral ceremony event Sayur Matua up the process of implementation, the envisaged role of the alliance system that is ToluSahundulan and Lima Simelungun Saodaran. They are incorporated in the kinship system is an integral and inseparable relationship brotherly rope while their parents died, and they intertwined relationship between good communication, mutual respect, love, and cooperation in the success of traditional events Sayur Matua death Keywords: Tortor Mangiligi, Sayur Matua ceremony, Social Values